Estimations of cosmological parameters from the observational variation of the fine structure constant - Zhai, Zhong-Xu; Liu, Xian-Ming; Zhang, Zhi-Song; Zhang, Tong-Jie (Research in astronomy and astrophysics, 2013)
We present constraints on the quintessence scalar field model from observational data of the variation of the fine structure constant obtained from the Keck telescope and VLT. Within the theoretical frame proposed by Bekenstein, the constraints on the parameters of the quintessence scalar field model are obtained. Considering the prior of Ωm0 as WMAP 7 suggests, we obtain various results from different sam- ples. Based on these results, we also calculate the probability density function of the coupling constant ζ. The best-fit values show a consistent relationship between ζ and the different experimental results. In our work, we test two different potential models, namely, the inverse power law potential and the exponential potential. The results show that both the large value of the parameters in the potential and the strong coupling can cause a variation in the fine structure constant.